The Role of Deposit Money Banks on the Growth of SMEs in Yakurr Local Government Area, Cross River State, Nigeria. - ojong, cornelius m; arikpo, oka felix; Anthony, Ogar (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This study examined the role of deposit money banks on the growth of SMEs in Yakurr Local Government Area, Cross River State, Nigeria. The objectives of the study were to examine the degree of relationship between deposit money banks credit, multiple taxations and government policies on the growth of SMEs. In order to achieve these objectives, three research hypotheses were tested at 5% level of significance. The survey research design was adopted and a well structured questionnaire was constructed to gather data for the study. The questionnaire was administered on 158 respondents comprising SMEs operators and banks staff. The Pearson product moment correlation statistical technique was applied. Findings resulting from the test revealed that deposit money banks credit had a significant relationship with the growth of SMEs. Multiple taxations and government policy summersault were found to significant affect SMEs growth. Based on these findings, the CBN was encouraged to mandate deposit money banks to set aside a certain percentage of their loanable funds for on lending to SMEs and to set up an enforcement team to ensure compliance by the banks. There was need to eliminate multiple taxation, reduce corporate taxes and strengthen government policy framework to impact significantly the growth of SMEs in Nigeria.